Pengaruh Audit Tenure, Ukuran Kantor Akuntan Publik, Ukuran Perusahaan dan Financial Distress terhadap Audit Delay - Vira Mustika Indreswari; Erinos NR (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to examine the effect of audit tenure, public accounting firm size, company size and financial distress on audit delay. This type of research is causal associative with a quantitative approach. The data used is obtained from the annual reports of companies in the property and real estate sectors listed on the Indonesia Stock Exchange 2017-2020. The sample selection method using purposive sampling obtained 181 samples from 47 companies. This study uses multiple linear regression analysis to test the hypothesis which is assisted by using the SPSS 25 program. The results show that audit tenure and the size of the public accounting firm have a significant and negative effect on audit delay, while company size and financial distress have a negative and significant effect on audit delay.